Qualitative and quantitative endothelium changes after cataract surgery: ultrasound phacoemulsification vs. nanolaser technique - Zbiba, Walid; Kharrat, Malek; Sayadi, Sana; Kallel, Zeineb; Marzouk, Ghassen (Frontiers in Medicine, 2023)
Purpose: Evaluate corneal endothelial cell density (ECD) and morphology, central corneal thickness (CCT), and best visual acuity (VA) using ultrasound (US) phacoemulsification or Nanosecond laser technique. Setting: Department of Ophthalmology, Nabeul, Tunisia. Methods: A Prospective cohort study including eyes with nuclear cataract, divided into two groups; Group 1 had conventional US, and group 2 had nanosecond laser. The ECD, coefficient of variation (CoV) in cell size, percentage of hexagonal cells, CCT and best VA were evaluated during 24 months. Results: Seventy-four eyes had uneventful surgery, 40 in group 1, 34 in group 2. The decline of the mean ECD was statistically significant in both groups and less important in group 2. The mean percentage of hexagonal decreased in group 1. In group 2, it remained almost stable. The mean CoV decreased with no notable differences after 2 years between the 2 groups. The difference in changes of the mean CoV and percentage of hexagonal cells between the groups was significant only during the six first months postoperatively. In both groups, the mean corneal thickness increased on the first day postoperatively then decreased more rapidly after 1 week in group 2, to find the initial values. There was no significant difference in VA at each follow-up between groups except for day1. Conclusion: Our study showed a lower corneal tissue trauma, and lower endothelial cell loss in the laser cataract surgery compared to phacoemulsification